Casting and rehabilitation versus skillful neglect for osteochondral lesions of the talus in the pediatric population: the care study, a multicenter, prospective comparative study - T. M.F. Buck; F. Smithuis; J. A.H. Steman; C. J.A. van Bergen; J. Dahmen; M. Terra; R. Hemke; Sjoerd A.S. Stufkens; M. Maas; Gino M.M.J. Kerkhoffs; P. A.A. Struijs (BMC Musculoskeletal Disorders)
Abstract Background Skeletally immature osteochondral lesions of the talus (OLTs) have a significant impact on the health status and quality of life of pediatric patients and the involved family. the current literature showed success in 4 out of 10 patients but it is currently unknown which type of non-operative management showed better clinical- and radiological outcomes. The aim of this study is to compare immobilization and supervised rehabilitation with a ‘skillful’’ neglect in the treatment for skeletally immature patients with an OLT. The hypothesis is that a period of immobilization and supervised rehabilitation will lead to better clinical and radiological outcomes compared to ‘’skillful’’ neglect. Methods Multicenter, prospective, comparative study. Skeletally immature children with an OLT will be assigned to the intervention or control group after a shared decision-making process. Patients in the intervention group will undergo a 4-week period of immobilization with normal casting and non-weightbearing, which is followed by 4 weeks of immobilization with a removable cast and weight bearing boot. Afterwards, they will receive a protocolled period of rehabilitation under supervision of a physical therapist. The control group will have a ‘skillful’’ neglect treatment. The main study outcome is the difference between the two groups on the Oxford Ankle and Foot Questionnaire for Children (OxAFQ-C). Secondary study outcomes are radiologic changes in terms of morphology and lesion size. Numeric Rating Scale (NRS) during weight bearing and quality of life measured with a Pediatrics Quality of Life (Peds-QL) and EuroQol-5 Dimension youth (EQ-5D-y). Discussion This protocol reports on the study design of the CARE Study and it aims to setup a study for evaluating different types of non-operative management in pediatric patients suffering an OLT. This study will compare clinical and radiological outcomes between two different non-operative strategies for treating OLTs in the skeletally immature population. Based on the results of this study, an evidence-based treatment protocol for non-operative management for pediatric OLTs can be provided. Trial registration This study is registered in the International Clinical Trial Registry Platform (ICTRP) with trial number NLOMON54282, date of registration 05192023.